Factors influencing college teachers to buy a car in Krishnagiri district: Tamilnadu - Priya, N.; Ravi, A. (International research journal of management, IT and social sciences, 2016)
It is evident that our country is growing in an excellent manner. As equal as to the developed nation, India is equally contributing in the car market and several companies came into India and challenging with Indian companies in the car segment. The automobile industry is one of the major areas in contributing tremendous growth in GDP. No doubt that car is an essential product for all income group and the college teachers are highly targeted customers for small car segment. The distributors are attracting the middle-income group for selling their small cars through the various attractive scheme in Krishnagiri district. Most of the teachers are from a rural background but having family support for improving their lifestyle. Having a car for a teacher, who is working in either private or Government College is a prestige issue and approaching the dealers for selecting their choice in car segments. According to the environmental condition and stressful traffic system, the road condition in rural areas is not improved for safety car driving. In India, it is a slogan of any individual to have a house, a car and an attractive lifestyle with the living place.